2013
DOI: 10.1155/2013/971203
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with HIV/AIDS in Sudan

Abstract: Objectives. To assess participants' knowledge about HIV/AIDS and to identify the factors associated with HIV/AIDS in Sudan. Methods. Observational cross-sectional study carried out at Omdurman National Voluntary Counseling and Testing Centre, Sudan covered 870 participants. Sociodemographic data as well as information related to sexual behavior were collected. Results. Most of the respondents were knowledgeable about the true transmission modes for AIDS virus. Very few respondents knew someone infected with AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 7 publications
2
32
0
Order By: Relevance
“…22,23 Educational attainment is highly correlated with condom use. 24,25 Higher education enables people to have greater access to prevention information about HIV/AIDS. This information may not be available to people with lower levels of education.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Educational attainment is highly correlated with condom use. 24,25 Higher education enables people to have greater access to prevention information about HIV/AIDS. This information may not be available to people with lower levels of education.…”
Section: Discussionmentioning
confidence: 99%
“…Divergent results have been published on the association between religion and HIV testing. Most studies were conducted among African populations and while some showed that religious affiliation was associated with an increased risk of HIV and a lower uptake of HIV testing (Addis et al, 2013;Hawkes et al, 2013;Mohamed & Mahfouz, 2013), others concluded that strong religious beliefs were unlikely to act as a barrier to accessing HIV testing (Fakoya et al, 2012). More broadly, religiosity has been reported to be negatively associated with use of sexual and reproductive health services (Hall, Moreau, & Trussell, 2012) and with lack of disclosure (Préau, Bouhnik, Roussiau, Lert, & Spire, 2008).…”
Section: Aids Care S89mentioning
confidence: 99%
“…Our results showed that single women are two time more likely to be infected by HIV than those who are 196 married or cohabiting. Others study had reported similar findings that peoples engaged in a marital 197 relationship are less exposed to HIV infection[9] This can be explained by the fact that individuals are more 198 likely to have multiple partners before marriage or after divorce or separation [10,11]. Moreover, due to…”
mentioning
confidence: 94%